2017
DOI: 10.1016/j.bbadis.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Search for KPNA7 cargo proteins in human cells reveals MVP and ZNF414 as novel regulators of cancer cell growth

Abstract: Karyopherin alpha 7 (KPNA7) belongs to a family of nuclear import proteins that recognize and bind nuclear localization signals (NLSs) in proteins to be transported to the nucleus. Previously we found that KPNA7 is overexpressed in a subset of pancreatic cancer cell lines and acts as a critical regulator of growth in these cells. This characteristic of KPNA7 is likely to be mediated by its cargo proteins that are still mainly unknown. Here, we used protein affinity chromatography in Hs700T and MIA PaCa-2 pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…104,105) Knockdown and knockout studies showed that KPNA7 was required for early embryogenesis. 72,84) Of note, mouse KPNA7 is localized in the nucleus or spindles in oocytes, depending on the maturation stage.…”
Section: Spindle Formationmentioning
confidence: 99%
“…104,105) Knockdown and knockout studies showed that KPNA7 was required for early embryogenesis. 72,84) Of note, mouse KPNA7 is localized in the nucleus or spindles in oocytes, depending on the maturation stage.…”
Section: Spindle Formationmentioning
confidence: 99%
“…Several studies have identified NLS-containing proteins that bind KPNA7, and in a few cases, demonstrated these are cargoes for KPNA7-dependent transport 34,35 . Reasoning that epilepsy reflects changes in neuronal activity, we used SILAC labeling and a straightforward MS/MS pipeline to identify KPNA7-interacting proteins in hiPSC-derived neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Given that KPNA7 mutations are associated with epilepsy 23 , we set out to identify KPNA7-interacting proteins using extracts of neuronal origin. Previous studies have used tandem mass spectrometry (MS/MS) to identify KPNA7-interacting proteins in HEK293 34 and pancreatic cancer cell lines 35 . Given the E344Q KPNA7 mutant shows a reduction in NLS binding, identification of KPNA7 cargo proteins could generate hypotheses for how mutation of KPNA7 affects neuronal differentiation.…”
Section: Identification Of Kpna7 Interacting Proteins In Neuronsmentioning
confidence: 99%
See 2 more Smart Citations